PEMETAAN CEPAT GENANGAN BANJIR MENGGUNAKAN TEKNOLOGI REMOTE SENSING - Tedy Pranadiarso; Entin Hidayah; Gusfan Halik (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
The existence of a flood inundation rapid map is needed in flood mitigation. This research is intended to map flood inundation quickly by utilizing satellite image technology. Sentinel 2 Level 1C technology uses before and after the flood. The extraction process uses the methods of NDWI (Normalized Difference Water Index) and MNDWI (Modified Normalized Difference Water Index). The result is treated with a threshold value by dividing the pixel value into flooded and unflooded areas. The performance model shows that the MNDWI method is more accurate than the NDWI method in producing flood inundation maps. Thus, the results of the MNDWI method are practical and able to map flood inundation quickly.Â